1859, NJ, An Ordinance to Prevent Firing of Guns, &c., in the City of Hoboken §§1-3, City Ordinances of Hoboken, NJ (1859). - (:unkn) unknown (General Publisher, 1859)
That no person or persons shall fire or discharge any cannon, gun, pistol, or fire-arms of any description, or fire, explode, or set off any squib cracker or other thing, containing powder or other combustibles or explosive material within the corporate limits of Hoboken, without the permission of the mayor. Also prohibited shooting ranges
--
Keywords: DISCHARGE; SHOOTING RANGES OR GALLERIES